The attacking style of teams is determinant of high-intensity actions of soccer referees - Paulo Sandi; Anderson S Teixeira; Gabriel S G Maia; Pedro V S Passos; Paulo V Souza; Carlo Castagna; Paulo H Borges; Juliano F Silva (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to examine the impact of the attacking style of teams and match outcome on the high-intensity activities (HIA) performed by Brazilian field referees (FRs) and assistant referees (ARs). The sample was composed of 20 FRs (age: 34.4 ± 5.9 years) and 36 ARs (age: 35.4 ± 6.3 years). Match activities derived from Global Position System (GPS) were collected from FRs and ARs during 41 official soccer matches over two seasons. A total of 3898 (FRs: 2118; ARs: 1780) actions were analyzed by video-motion to determine attacking style: counterattack (CA), fast attack (FA) and positional attack (PA). Match outcome was assessed as final match outcome (home win, draw and away win) and goal difference (GD) (0, 1 and ≥ 2). Significance level was set ρ < 0,05. Higher proportion of HIA was observed during CA (FRs: 60.7%; ARs: 50.6%) when compared to FA and PA. CA elicited longer HIA in terms of distance and duration than the other attacking styles analyzed. FRs covered significantly (p = 0.01) longer total distance (TD) when the away team won the match than in other conditions. In addition, GD 1 and GD 0 resulted in longer TD (p=0.01) and distance at sprinting (SPR) (p=0.04), respectively. These results provide valuable insights to the influence of different match factors on the performance of referees during soccer matches.